First comparative genomic characterization of the MSSA ST398 lineage detected in aquaculture and other reservoirs - Salgueiro, Vanessa; Manageiro, Vera; Bandarra, Narcisa M.; Ferreira, Eugénia; Clemente, Lurdes; Caniça, Manuela (Frontiers in Microbiology, 2023)
Staphylococcus aureus ST398 can cause diseases in several different animals. In this study we analyzed ten S. aureus ST398 previously collected in three different reservoirs in Portugal (humans, gilthead seabream from aquaculture and dolphin from a zoo). Strains tested against sixteen antibiotics, by disk diffusion or minimum inhibitory concentration, showed decreased susceptibility to benzylpenicillin (all strains from gilthead seabream and dolphin) and to erythromycin (nine strains), and susceptibility to cefoxitin (methicillin-susceptible S. aureus, MSSA). All strains from aquaculture belonged to the same spa type, t2383, whereas strains from the dolphin and humans belonged to spa type t571. A more detailed analysis using single nucleotide polymorphisms (SNPs)-based tree and a heat map, showed that all strains from aquaculture origin were highly related with each other and the strains from dolphin and humans were more distinct, although they were very similar in ARG, VF and MGE content. Mutations F3I and A100V in glpT gene and D278E and E291D in murA gene were identified in nine fosfomycin susceptible strains. The blaZ gene was also detected in six of the seven animal strains. The study of the genetic environment of erm(T)-type (found in nine S. aureus strains) allowed the identification of MGE (rep13-type plasmids and IS431R-type), presumably involved in the mobilization of this gene. All strains showed genes encoding efflux pumps from major facilitator superfamily (e.g., arlR, lmrS-type and norA/B-type), ATP-binding cassettes (ABC; mgrA) and multidrug and toxic compound extrusion (MATE; mepA/R-type) families, all associated to decreased susceptibility to antibiotics/disinfectants. Moreover, genes related with tolerance to heavy metals (cadD), and several VF (e.g., scn, aur, hlgA/B/C and hlb) were also identified. Insertion sequences, prophages, and plasmids made up the mobilome, some of them associated with ARG, VF and genes related with tolerance to heavy metals. This study highlights that S. aureus ST398 can be a reservoir of several ARG, heavy metals resistance genes and VF, which are essential in the adaption and survival of the bacterium in the different environments and an active agent in its dissemination. It makes an important contribution to understanding the extent of the spread of antimicrobial resistance, as well